Nilai-Nilai Etnopedagogi Dalam Perspektif Falsafah Al-Qur’an - Muhammad Fikran Said; Rahmi Damis; Muhammad Yusuf (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze ethnopedagogical values from the perspective of the philosophy of the Qur’an and their relevance to character education development. The research employed a qualitative approach using a library research method. Data sources were obtained from the Qur’an, interpretation books, scientific journals, books, and other relevant literature related to ethnopedagogy and Islamic education. Data collection techniques were conducted through documentation and literature review, while data analysis used content analysis techniques. The results revealed that ethnopedagogical values such as mutual cooperation, deliberation, tolerance, politeness, and respect for parents are closely related to educational values contained in the Qur’an. The integration of local culture and the philosophy of the Qur’an can create contextual, humanistic, and character-oriented education. Furthermore, ethnopedagogical-based education can serve as a solution to the challenges of globalization that may erode cultural identity and moral values in society. This study concludes that the implementation of ethnopedagogy from the perspective of the Qur’an has strong relevance in developing a generation that is characterized, religious, and appreciative of local culture.